What Are the Key Points of Treatment for Cases of Mild Cognitive Impairment? Based on the Evaluation of Cognitive Function Tasks in the ADASJcog - Yoshihiko Yoshii (Karger Publishers, 2021)
Background/Aims: The aims of this study were to identify the degree of atrophy of the hippocampus in image findings and which cognitive function items should be focused on when treating mild cognitive impairment. Methods: A total of 66 cases with mild cognitive impairment were included in the study over a 1.5-year observation period. MR images were used to assess hippocampal atrophy, and cognitive function was assessed by the ADASJcog test. Results: In the mild dementia group, there was a hierarchical difference in the 4 cognitive impairments in which each degree was significantly higher hierarchically. In the normally improved group, memory and act dysfunction was significantly improved, and in deteriorated cases, memory, orientation, and act dysfunction increased significantly. The normally improved group tended to have lighter hippocampal atrophy than the deteriorating group. Discussion: In early treatment of mild cognitive impairment, it is important to focus on which cognitive items to treat, but there are no reports that present them numerically. Because it is not clear, there may be a risk that dementia may progress due to stunned treatment. It became clear that it was meaningful to show it, and it was the orientation and act function. Conclusion: It was suggested that hippocampal atrophy should be kept within the normal range and that the key treatment was mainly to improve memory and act dysfunction without reducing orientation function.